Effectiveness of Banana Leaves (Musa Paradisiaca L) as A Bandage for Healing Diabetes Wounds - Simamora, Hengky; Tanjung, Dudut; Yuandani, Yuandani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes mellitus is a chronic degenerative disease characterized by increased blood glucose levels that exceed normal limits. Complications often experienced by patients with diabetes mellitus are wounds. Wounds that are difficult to heal can result in amputation. Banana leaves have antioxidant activity and biological functions including anti-diabetic and have been proven to be a source of bioactive compounds that function to stop or inhibit the growth of bacteria and fungi that can cause infection in wound tissue. Objective: to analyze the effectiveness of banana leaves as a dressing in the wound healing process in diabetic patients. The study was a quasi-experiment with a pre-post control design. Thirty-two were applied in this study, 16 were intervention group and 16 were control group. Data were collected using the Bates-Jensen Wound Assessment Tool and analyzed using the Wilcoxon signed-rank test. There is a significant difference in wound healing in the intervention group before and after the use of banana leaves as a dressing (p<0.001). The results of this study can be a basis for nurses in applying or implementing banana leaves as wound dressings for the healing process of diabetic wounds, both chronic and acute wounds, and these results can support nurses in carrying out independent nursing care.